Photosensitivity reactions in the elderly population: questionnaire-based survey and literature review - Korzeniowska K; Cieślewicz A; Chmara E; Jabłecka A; Pawlaczyk M (Dove Medical Press, 2019)
Katarzyna Korzeniowska,1 Artur Cieślewicz,1 Ewa Chmara,1 Anna Jabłecka,1 Mariola Pawlaczyk2 1Department of Clinical Pharmacology, Poznan University of Medical Sciences, Poznań 61-848, Poland; 2Department of Geriatric Medicine and Gerontology, Poznan University of Medical Sciences, Poznań 60-781, PolandCorrespondence: Artur CieślewiczDepartment of Clinical Pharmacology, Poznan University of Medical Sciences, Długa 1/2 Street, Poznań 61-848, PolandTel +48 61 854 9216Fax +48 61 853 3161Email artcies@ump.edu.plPurpose: Older people are at risk of developing adverse drug reactions, including photosensitivity reactions. Therefore, the aim of the study was to assess the use of potentially photosensitizing medications and photoprotection in the elderly population.Patients and methods: Three hundred and fifty-six respondents (223 [63%] women and 133 [37%] men) aged ≥65 years filled in the original questionnaire concerning photosensitivity reactions to drugs. The diagnosis of drug-induced photosensitivity was based on medical history and clinical examination.Results and conclusion: We found that drugs potentially causing phototoxic/photoallergic reactions comprised more than one fifth of all drugs used by the participants. The most numerous group was patients treated with 3–5 drugs potentially causing phototoxic/photoallergic reactions simultaneously. Of all drugs, ketoprofen was found to cause the highest number of photosensitivity reactions. Cutaneous adverse reactions were also observed for hydrochlorothiazide, atorvastatin, simvastatin, telmisartan, and metformin. Moreover, it was found that the incidence of photosensitivity reactions can be significantly reduced by using proper photoprotection.Keywords: photoprotection, elderly population, photosensitivity, phototoxicity, photoallergy